Aestheticism and the romantic absolute: new mythology of early German romanticism - Küçükarslan, Onur. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2008., 2008)
This study claims that Early German Romanticism introduced an authentic and independent philosophical perspective by refusing various dualisms of Kant and Fichte’s postulation of first principles and foundations of subjectivist aesthetic tradition. It is maintained that the preservation of the ground of the subject while rejecting the priority of the Ego; and the defense of Absolutism without the refusal of pluralism makes Early German Romanticism an actual and strong alternative among contemporary criticisms of modernity. The common misunderstanding that Early German Romanticism belongs to the anti-rationalist strand is rejected and it is shown that the Romantics preserved, even radicalized some of the fundamental ideals of Enlightenment and the principles of the rationalist school. It is maintained that the Romantics stressed the importance of individuality in reaction against the formalism of Kant’s ethics and that they invented a moral program based on sensibility and aesthetic sense following Schiller. Their argument that it is only art which can reveal the truth and their rejection of the individualism of contract theories in politics are other major discussions of the thesis. A discussion of the philosophical programs of Kant, Fichte and Schiller and the comparison of major Romantic arguments with these is the major methodological strategy of the study.|Keywords: Romanticism, Schlegel, Novalis, irony, genius, Absolute.
Keywords: Romanticism -- Germany.; Philosophy, German -- 18th century.; Irony in literature.; Absolute, The.